Efektivitas Perineal Massage Dalam Menurunkan Tingkat Laserasi Perineum Pada Ibu Postpartum Primipara - Elvira Trista Subroto; Fitriani Sangkala (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Perineal laceration is a rupture in the birth canal or tearing of tissue in the perineal area that is in the area between the vaginal and muscles, which occurs due to labor too quickly and the baby's head is born large. Aims: To identify a decrease in the rate of perineal lacerations in postpartum primipara mothers. Method: The design of this research methodology approach is a literature review to determine various quantitative and qualitative evidence using electronic databases, namely: Pubmed, Google Scholar, and Garuda, then restrictions based on criteria include producing 876 respondents. The analysis uses an extracted data map on the article's search results table including author, year of publication, country, destination, sample, research design, type of research, length of intervention, results, and research conclusions. Results: Showed that this action effectively lowers the degree of laceration and maintains the laceration's wholeness with the appropriate implementation of the recommended time. Conclusion: This therapy is safe and very retired to be included in the list of classes of pregnant women and is recommended to do health education for mothers to increase knowledge on how to prevent perineal lacerations.